The role of psychological factors in the career of the independent dancer - Aujla, Imogen; Farrer, Rachel (Frontiers in Psychology, 2015)
Previous research indicates that psychological factors such as motivation and mental skills play an important role in relation to performance and to negotiating talent development stages. However, little is known about these factors in dance, particularly with regard to the independent dancer whose career may involve multiple roles, varied work patterns and periods of instability. The aim of this study was to explore dancers’ motivation to work in an independent capacity, and the extent to which dancers’ psychological characteristics and skills enabled them to navigate a career in this demanding sector. In-depth semi-structured interviews were conducted with 14 dancers at different stages of their careers. Interviews were transcribed verbatim and content analyzed. Analysis revealed that the dancers were intrinsically motivated and highly committed to the profession. Working in the independent sector offered dancers opportunities for growth and fulfillment; they appreciated the autonomy, flexibility and freedom that the independent career afforded, as well as working with new people across roles and disciplines. In order to overcome the various challenges associated with the independent role, optimism, self-belief, social support and career management skills were crucial. The mental skills reported by the participants had developed gradually in response to the demands that they faced. Therefore, mental skills training could be invaluable for dancers to help them successfully negotiate the independent sector.